Bionic reticulated nanofiber composite coating, preparation method thereof and application in repairing infectious bone defects
By constructing a mesh-like nanofiber composite coating on the implant surface, the problem of bacterial biofilm removal in infected bone defects was solved, achieving synergistic regulation of antibacterial biofilm, anti-oxidative stress and osteopromoting effects, thus improving the therapeutic effect of bone implant materials and the long-term stability of implants.
Patent Information
- Application Number
- CN202511891825.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-16
- Publication Date
- 2026-03-24
- Estimated Expiration
- 2045-12-16
AI Technical Summary
Existing bone implant materials are difficult to effectively remove bacterial biofilms in the treatment of infected bone defects, resulting in a high recurrence rate of infection. Furthermore, the use of inorganic nanomaterials may have adverse effects on normal bone tissue, and the thickness of hydrogel materials is difficult to precisely control in bone repair, affecting the contact between the implant and bone tissue.
A layer-by-layer self-assembly technique is used to construct a mesh-like nanofiber composite coating on the implant surface. Through the alternating deposition of lysozyme amyloid protein fibers and polyphenolic substances, and the loading of bioactive metal ions, a multifunctional coating with antibacterial biofilm, anti-oxidative stress and osteopromoting properties is formed. The mesh structure of lysozyme amyloid protein fibers is used to mimic the extracellular matrix, and combined with polyphenolic antioxidants and metal ions, to achieve highly selective antibacterial and osteopromoting regulation.
It significantly reduces bacterial biofilm formation, removes excess ROS, promotes osteoblast adhesion and differentiation, enhances bone tissue regeneration, reduces the risk of recurrence of infected bone defects, and improves the long-term survival rate of implants.
Smart Images

Figure CN121338108B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials and relates to a biomimetic mesh nanofiber composite coating, its preparation method, and its application in the repair of infected bone defects. Background Technology
[0002] Currently, bone regeneration and repair has become a global issue. Bone grafting is the second most common tissue transplantation procedure after blood transfusion, requiring a large amount of transplanted bone or bone substitute materials annually. While bone tissue generally possesses a certain degree of self-healing ability, bone defects exceeding a critical size necessitate comprehensive repair through implant transplantation. Clinically used bone repair implants primarily include autologous bone, allogeneic bone, and artificial bone. Currently, artificial bone implants have become an important application in clinical bone defect repair.
[0003] In orthopedic clinics, enhancing osseointegration at the interface between implants and infected bone tissue is a major challenge. Large, infected bone defects are difficult to treat and seriously endanger patients' lives and health. Bacterial resistance and the formation of defensive bacterial biofilms lead to recurrent infections such as osteomyelitis. According to studies on fracture-related infections (FRIs), the recurrence rate of clinical bone defect infections is as high as 8%, and the amputation rate is 3%. Bacteria are encapsulated in a bacterial biofilm matrix composed of extracellular polysaccharides, amyloid proteins, and nucleic acids, forming a strong physical and biochemical barrier. This structure leads to a dramatic increase in bacterial resistance to host immune clearance and antibiotics, with resistance levels increasing by 10 to 1000 times, greatly increasing the difficulty of clinical control. The biofilm formed by bacterial adhesion and proliferation on the surface of bone implants is the main reason why implant-related infections are difficult to eradicate completely. Loading the surface of bone implants with antibiotics, antimicrobial proteins, or peptides can inhibit bacterial growth to some extent, but due to drug resistance, it is still difficult to eliminate the bacterial biofilm. Current mainstream treatments for infected bone defects typically rely on inorganic nanomaterials to generate highly reactive oxygen species (ROS) that kill bacterial biofilms. However, inorganic nanomaterials are generally difficult to metabolize, posing potential biosafety issues, and the oxidative stress microenvironment created by highly reactive oxygen species (ROS) can adversely affect normal bone tissue. Excessive ROS generated by inorganic antibacterial nanomaterials can induce excessive inflammatory responses at the site of infected bone defects, severely hindering bone regeneration and repair.
[0004] Lysozyme amyloid fibers are fibrous materials formed by the self-assembly polymerization of lysozyme proteins. They exhibit excellent resistance to bacterial biofilms and high stability. Interfacial modification based on lysozyme amyloid fibers can significantly improve the antibacterial biofilm activity of bone implant surfaces. Currently, lysozyme amyloid is used as a hydrogel material in fields such as skin repair and intestinal therapy. However, for bone repair, hydrogel materials face technical challenges, including difficulty in precisely controlling thickness, a "cushioning effect" that hinders contact between the implant and bone tissue, and unsuitability for functionalizing the surface of orthopedic implants. Summary of the Invention
[0005] Therefore, the purpose of this invention is to construct a biomimetic antibacterial biofilm infection-antioxidative stress-osteogenic mesh coating based on lysozyme amyloid fibers. This invention proposes a multifunctional lysozyme amyloid fiber coating system that synergistically regulates the infection microenvironment, removes excess ROS, and promotes osteogenic growth, aiming to provide a new solution for the regeneration and repair of infected bone defects. The coating's unique mesh nanofiber structure, mimicking the extracellular matrix, promotes osteoblast adhesion and differentiation, and its bacterial biofilm-like amyloid fiber structure traps and kills bacteria (Gram-negative and Gram-positive), achieving highly selective antibacterial and osteogenic regulation. The mesh antibacterial coating is internally loaded with polyphenolic antioxidants and antibacterial substances such as tannic acid (TA), which can resist oxidative stress and efficiently destroy and remove bacterial biofilms, exhibiting broad-spectrum antibacterial activity against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. Furthermore, natural polyphenolic compounds (TA, etc.) combined with bioactive Mg... 2+ We constructed a multifunctional synergistic coating system that combines anti-infection, anti-oxidative stress, angiogenesis, and osteoproliferation to achieve comprehensive regulation of the microenvironment of infected bone defects.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This invention provides a mesh nanofiber composite coating, wherein the composite coating is prepared by lysozyme amyloid protein fibers through layer-by-layer self-assembly and alternating deposition of polyphenolic substances on the surface of an implant substrate, and by coordination of bioactive metal ions with polyphenolic hydroxyl groups;
[0008] Preferably, the polyphenolic substance is any one of tannic acid, epicatechin gallate, and gallic acid;
[0009] Preferably, the bioactive metal ion is Mg. 2+ 、Sr 2+ Zn 2+ Cu 2+ Any one of them;
[0010] Preferably, the composite coating has 4-8 layers;
[0011] The preparation method of the mesh nanofiber composite coating includes the following steps:
[0012] S1: Prepare a 50 mM glycine aqueous solution, adjust the pH of the solution to 2, dissolve lysozyme in the glycine solution and mix well. The lysozyme concentration is 10 mg / mL. Heat and stir at 65 ℃ for 0.5-4 h, then transfer to a dialysis bag for dialysis. After freeze-drying, obtain lysozyme amyloid protein fibers.
[0013] S2: Lysozyme amyloid fibrous material, polyphenolic substances, and polyethyleneimine were dissolved in 10mM acetate buffer NaAc-HAc, respectively. The substrate was immersed in the polyethyleneimine solution for about 1 hour to form an initial layer. Subsequently, the above substrate was alternately immersed in the polyphenolic substance solution for 0.5-4 hours and then immersed in the lysozyme amyloid fibrous material solution for 0.5 hours to prepare a mesh nanofiber structure coating.
[0014] S3: Immerse the mesh nanofiber structure coating prepared in step S2 in a bioactive metal ion solution for 0.5 h to prepare the mesh nanofiber composite coating;
[0015] Preferably, the concentrations of the lysozyme amyloid cellulose, polyphenols, and polyethyleneimine are 1-10 mg / mL;
[0016] Preferably, the substrate is any one of stainless steel, magnesium alloy, or titanium alloy support.
[0017] Furthermore, the application of the aforementioned biomimetic mesh nanofiber composite coating in the preparation of medical materials or drugs;
[0018] Preferably, the biomimetic mesh nanofiber composite coating is used in the preparation of medical materials for infectious bone defects.
[0019] The beneficial effects of this invention are as follows:
[0020] (1) Lysozyme amyloid protein fiber (LAPF) has a unique nanofiber network structure. The LAPF coating has a micro- and nano-porous hydrophilic surface, and the bioactive metal ion Mg 2+ Successful loading and uniform distribution within the tissue provide an ideal osteogenic microenvironment for subsequent cell adhesion and tissue ingrowth.
[0021] (2) LAPF can effectively disrupt bacterial cell membranes through its high positive charge and "Trojan horse" trapping mechanism. Plate counts showed that the LAPF mesh coating had good bactericidal effects against both Staphylococcus aureus and Escherichia coli.
[0022] (3) SEM observation and crystal violet staining further confirmed that (TA / LAPF)8+Mg 2+ The coating can significantly inhibit bacterial adhesion and disrupt biofilm structure.
[0023] (4) Regarding antioxidant stress, (TA / LAPF)8+Mg 2+ The coating achieves 83.5% ABTS. + • It reduces free radical scavenging rate and decreases ROS levels in H2O2-stimulated bone marrow mesenchymal stem cells (BMSCs) by approximately 60%.
[0024] (5) In terms of promoting bone formation, the LAPF mesh coating has good biocompatibility, which increases the number of BMSCs adhering to 2.5 times that of the control group.
[0025] (6) At the same time, in Mg 2+ Under the synergistic effect, (TA / LAPF)8+Mg 2+ The coating can significantly enhance alkaline phosphatase (ALP) activity and promote calcium nodule deposition.
[0026] (7) Regarding angiogenesis, (TA / LAPF)8+Mg 2+ The coating promotes the migration of human umbilical vein endothelial cells (HUVECs) with a migration rate as high as 83.2%, demonstrating good angiogenesis-promoting ability.
[0027] (8) In a rat model of infectious bone defect one week after implantation, (TA / LAPF)8+Mg 2+ The bacterial count around the implant in the coated group was significantly reduced by 80% compared to the control group.
[0028] (9) Six weeks after implantation, Micro-CT analysis and tissue staining showed that (TA / LAPF)8+Mg 2+ The bone volume fraction (BV / TV) was significantly increased in all coated groups. This indicates that (TA / LAPF)8+Mg 2+ The coating demonstrates a dual effect of significant antibacterial activity and bone regeneration promotion in vivo.
[0029] This invention constructs a biomimetic antibacterial and osteogenic active coating that integrates functions of "antibacterial biofilm infection, anti-oxidative stress, angiogenesis, and bone regeneration promotion." It can create a local microenvironment conducive to osseointegration at the implant / bone tissue interface, effectively reducing the risk of poor osseointegration in infected bone defects. Compared to hydrogel materials prepared by simple mixing methods, the coating prepared by layer-by-layer self-assembly technology allows for precise control of thickness by adjusting the number of assembled layers, optimizing surface bioactivity while essentially preserving the mechanical strength of the bone implant substrate. This offers significant advantages in bone implant surface modification applications. The layer-by-layer self-assembly technology is used to prepare a lysozyme amyloid fiber coating loaded with antioxidant polyphenols and bioactive metal ions, achieving synergistic effects of antibacterial biofilm infection, anti-oxidative stress, and osteogenic integration, thus addressing the technical problem of poor osseointegration in implants with infected bone defects. This strategy has significant clinical implications for improving the long-term survival rate and treatment success rate of implants in high-risk patients with complex trauma (such as open fractures) or systemic diseases (such as osteoporosis and diabetes).
[0030] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0031] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:
[0032] Figure 1 Atomic force microscopy (AFM) image of LAPF;
[0033] Figure 2 SEM scans of different LAPF mesh coatings;
[0034] Figure 3 (TA / LAPF)8+Mg 2+ Elemental distribution corresponding to the microstructure of the coating (Scale bar = 200nm);
[0035] Figure 4 (a) Escherichia coli and Staphylococcus aureus compared with the control group and (TA / LAPF)8+Mg 2+ (a) Crystal violet staining images of the co-cultured coating group (Scale bar = 200 μm); (b) Percentage of Escherichia coli biofilm area in different sample groups; (c) Percentage of Staphylococcus aureus biofilm area in different sample groups (*** P < 0.001, n = 3);
[0036] Figure 5 To illustrate the in vitro cell behavior of LAPF-coated surfaces, (a) BMSCs cells were observed in the control group and (TA / LAPF)8+Mg 2+ Fluorescence micrographs of early adhesion on the surface of the coating group (Scale bar = 100 μm) (b) Schematic diagram of cell adhesion (c) Statistical graph of cell number per square centimeter (* P<0.05, ** P<0.01, n=3);
[0037] Figure 6 (a) HUVEC scratch assay (Scale bar = 100 μm) for the control group and the coated group, and (b) endothelial cell migration rate (* P < 0.05, ** P < 0.01, n = 3).
[0038] Figure 7 (TA / LAPF)8+Mg 2+ In vitro osteogenic effects of the coating; (a) control group and (TA / LAPF)8+Mg 2+ (a) Alkaline phosphatase staining images of the coated group (Scale bar = 100 μm); (b) Control group and (TA / LAPF)8+Mg 2+ Alizarin red staining images of calcium nodules in the coating group (Scale bar = 100 μm); (c) Quantitative analysis of alkaline phosphatase staining area; (d) Quantitative analysis of calcium nodule staining area (* P<0.05, ** P<0.01, *** P<0.001, n=3);
[0039] Figure 8 It is a pure titanium rod and (TA / LAPF)8+Mg 2+ SEM images of coated composite titanium rods at different scales;
[0040] Figure 9 Pure titanium mesh and (TA / LAPF)8+Mg 2+ SEM images of coated composite titanium mesh at different scales;
[0041] Figure 10 For (a) 1-4 Bone defect implantation surgery procedure (b) One week later, control group and (TA / LAPF)8+Mg 2+ Images of Staphylococcus aureus plate coatings in the coating group;
[0042] Figure 11 For (a) Control and (TA / LAPF)8+Mg implanted 6 weeks later 2+ (a) Pseudocolor image of bone defect in coated group, (b) BV / TV bone volume fraction histogram (**) P <0.01, n=3);
[0043] Figure 12 Histological evaluation of osseointegration 6 weeks after implantation; H&E and Masson staining images around implants in different groups, with black rectangles representing magnified image areas and red arrows indicating areas of new bone formation. Detailed Implementation
[0044] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0045] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0046] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0047] Example 1
[0048] Weigh 0.188 g of glycine and dissolve it in 30 mL of deionized water. Adjust the pH of the solution to 2 with hydrochloric acid, and then bring the volume to 50 mL with deionized water to prepare a 50 mM solution. Weigh 0.5 g of egg white lysozyme and dissolve it in 50 mL of the glycine solution, mixing well to prepare a 10 mg / mL solution. Heat and stir the solution at 65 °C and 1000 rpm for 0.5, 1, 2, 3, and 4 hours, respectively, and transfer the solution to a dialysis bag for dialysis for 4 days. Change the water twice a day, morning and evening. After 4 days, transfer the solution to a -80 °C freezer. After freezing, freeze-dry the solution using a lyophilizer. After 2 days, collect the LAPF product.
[0049] The surface morphology of amyloid protein was analyzed by imaging in air using an atomic force microscope (AFM, SPM-9700, Shimadzu, Japan). Lysozyme and LAPF samples were weighed and dissolved in deionized water to prepare a concentration of 0.01 mg / mL. The solution was sonicated for 5 min, and 500 μL of the solution was applied to freshly peeled mica sheets. Each sample was allowed to stand for 3 min to adsorb the mica, and then the mica sheets were allowed to air dry at room temperature.
[0050] AFM results showed that the hydrothermal reaction conditions (65°C, pH=2, 4 h) successfully induced lysozyme molecules to undergo highly ordered self-assembly into a fibrous morphology (e.g., Figure 1 (As shown).
[0051] Weigh 0.05 g of lyophilized LAPF sample, tannic acid (TA), and polyethyleneimine (PEI). The LAPF sample was dissolved in 50 mL of deionized water, and the TA and PEI were dissolved in 10 mM NaAc-HAc acetate buffer (pH=6), each at a concentration of 1 mg / mL. First, the silicon wafer substrate was immersed in the PEI solution for approximately 1 h to form an initial layer. Subsequently, the substrate was alternately immersed in TA solution for 30 min, followed by immersion in LAPF solution for 30 min, labeled as (TA / LAPF). n Here, n represents the number of bilayer cycles. In this embodiment, 4-layer and 8-layer structures (TA / LAPF)4 and (TA / LAPF)8 were used to investigate the effect of the number of layers. Furthermore, between each layer in the layer-by-layer self-assembly process, the sample was washed with 10 mM NaAc-HAc (pH=6) assembly buffer. Finally, the (TA / LAPF)8 coating was immersed in MgCl2 solution (200 mM) for 30 min to incorporate Mg. 2+ And labeled as (TA / LAPF)8+Mg 2+ (The coating preparations mentioned in the subsequent experimental data were all prepared using this method and conditions). This example was observed using a scanning electron microscope (SEM) (e.g., Figure 2(As shown). The results indicate that the TA / LAPF coating forms a network structure.
[0052] EDS spectrum (e.g.) Figure 3 (As shown) (TA / LAPF)8+Mg 2+ The coating group clearly demonstrates the uniform distribution of C (carbon), N (nitrogen), and O (oxygen) elements on the coating surface using different colors. In addition, (TA / LAPF)8+Mg 2+ Mg is also present in the coating group 2+ Element, and Mg 2+ The distribution of Mg highly overlaps with that of C, N, and O elements. This result directly proves that Mg... 2+ It was successfully loaded into TA / LAPF and is consistent with the fiber morphology.
[0053] Test Example 1
[0054] Crystal violet staining of bacterial membranes:
[0055] Second-generation Escherichia coli and Staphylococcus aureus bacterial suspensions were serially diluted using LB liquid medium to a concentration of approximately 1 × 10⁻⁶. 6 CFU / mL, take 2 mL of the diluted bacterial solution and add it to each group of (TA / LAPF)4, (TA / LAPF)8, (TA / LAPF)8+Mg 2+ The coating was co-cultured in a 24-well plate oven for 36 h to observe the bacterial biofilm formation. The bacterial culture in the well plate was gently removed with a 1 mL syringe to prevent damage to the bacterial biofilm. 4% paraformaldehyde fixative was added for 20 min to fix the bacterial biofilm. After removing the fixative and air-drying, 2% crystal violet solution was added for 5 min to incubate. The staining solution was removed, and the plate was repeatedly washed with PBS until no purple liquid was left. After air-drying, the stained sample was photographed.
[0056] The results of the crystal violet staining experiment (such as...) Figure 4 As shown in the figure, in the control group, bacterial biofilms of both *E. coli* and *Staphylococcus aureus* were stained deep purple and were very dense, almost filling the entire field of view. With the increase of LAPF (TA / LAPF), only a small amount of bacterial film staining was visible in the 8-coated group, indicating that only a very small number of bacterial colonies could survive and grow weakly on the coating surface, almost unable to form a continuous, structured biofilm. This demonstrates that increasing the LAPF loading (number of layers) linearly enhances its anti-biofilm efficacy. 2+ The antibacterial function of the subsequent coating group was slightly enhanced. This confirms that all LAPF coatings loaded on the substrate surface have good antibacterial biofilm effects.
[0057] LAPF mesh coating cell adhesion and morphology:
[0058] First, (TA / LAPF)4, (TA / LAPF)8, (TA / LAPF)8+Mg 2+ The coating was applied using a glass slide as a substrate and then transferred to a clean bench for UV sterilization. Well-grown BMSCs were digested, centrifuged, and resuspended into a single-cell suspension, then treated with a concentration of 3 × 10⁻⁶ cells / mL. 4 BMSCs at a concentration of [cell / mL] were seeded into each group of coatings and incubated in a 37°C, 5% CO2 incubator. After 4 hours, the culture medium was removed, and the cells were washed twice with PBS, then incubated with 4% paraformaldehyde tissue fixative for 20 minutes, followed by two more washes with PBS. 300 μL of 0.2% Triton X-100 solution was added and incubated in the dark for 10 minutes, followed by two more washes with PBS. Rhodamine dye was added according to the drug instructions and incubated in the dark for 1 hour, followed by three more washes with PBS. DAPI was added and incubated in the dark for 15 minutes, followed by further washing with PBS. The cells were then mounted using anti-fluorescence quenching mounting medium. Images were taken under an inverted fluorescence microscope, showing blue fluorescence in the cell nuclei and red fluorescence in the cytoskeleton.
[0059] Early adhesion of BMSCs to the TA / LAPF coating was assessed using fluorescence images 4 hours after BMSC inoculation. Figure 5 As shown, fluorescence imaging and cell adhesion count revealed that some BMSCs adhered to the substrate surface in the control group, but their cell morphology was elliptical and insufficiently spread. The (TA / LAPF)4 coating group showed significantly more adhered cells than the control group, with improved cell morphology, extended pseudopodia, and a spread-out appearance. The (TA / LAPF)8 coating group and (TA / LAPF)8+Mg... 2+ The number of adherent cells further increased, exceeding that of the control group and the (TA / LAPF)4 coating group. These cells had a larger spreading area and exhibited a well-defined spindle-shaped or polygonal morphology, typical characteristics of healthy and tightly adhered cells. There was no significant difference in the number of adherent cells between the two groups, indicating that Mg... 2+ The incorporation of [a substance] has almost no effect on cell adhesion, proving that its coating has good cell adhesion ability.
[0060] LAPF mesh coating in vitro cell migration assay:
[0061] HUVECs cells were loaded at 2.5 × 10⁻⁶. 4The cells were seeded at a density of 1 cell / mL in 24-well plates. During culture, when the cell density reached 90%, the cells were starved, and the complete medium was replaced with basal medium. The cells were cultured overnight. Two lines were drawn perpendicular to the wells using a 200 μL pipette tip. Excess cell debris was gently washed away with PBS. Cells containing (TA / LAPF)4, (TA / LAPF)8, and (TA / LAPF)8+Mg were added. 2+ Cells were cultured using the coating extract (soaked in DMEM for 5 days), while the control group contained only DMEM. The scratched areas of each group were photographed using an inverted microscope at 0 h, 12 h, and 24 h in a cell culture incubator, and their migration rate was calculated.
[0062] Migration rate = (Initial scratch width - Final scratch width) / Initial scratch width × 100%
[0063] like Figure 6 As shown, the scratch width was consistent across all groups at 0 h. After 12 h of incubation, the scratch area decreased in both the control group and all LAPF coating groups. Quantitative calculations showed that (TA / LAPF)4 and (TA / LAPF)8 coatings exhibited better scratch healing performance at 12 h compared to the control group, with migration rates of 30.53% and 43.54%, respectively. Meanwhile, (TA / LAPF)8+Mg... 2+ The control group showed the best results, with a migration rate of 54.5%. As the culture time reached 24 hours, although the scratch area of the control group, (TA / LAPF)4, and (TA / LAPF)8 coating groups further decreased, significant scratch gaps still remained. Meanwhile, the (TA / LAPF)8+Mg group showed the best results. 2+ Scratches on the coating healed significantly after 24 hours of incubation, with a migration rate of 83.20%. The results indicate that Mg... 2+ It helps enhance the migration and vascularization of endothelial cells, Mg 2+ Endothelial cell migration can be strongly promoted by activating the CGRP (calcitonin gene-related peptide) signaling pathway. After binding to its receptor, CGRP activates downstream signaling pathways such as PKA and Akt, regulating cytoskeleton rearrangement and pseudopodia formation, thereby accelerating cell motility. Experimental results show that Mg... 2+ The introduction of this ingredient can further enhance the migration ability of endothelial cells on the TA / LAPF coating surface.
[0064] In vitro angiogenesis experiment of LAPF mesh coating:
[0065] Thaw the Matrix matrix gel overnight at 4 ℃. Place the pipette tips and box in a -20 ℃ freezer. The next day, pipette 50 μL of Matrix matrix gel into each well of a 96-well plate along the inner wall of the plate, taking care to prevent air bubbles. Incubate for 1 h. Then, culture HUVECs cells at a rate of 2 × 10⁶ cells / well. 4 The cells were seeded at a density of 1 cell / mL in 96-well plates, and 300 μL of a mixture containing (TA / LAPF)4, (TA / LAPF)8, and (TA / LAPF)8+Mg was added to each well. 2+ The coating was cultured in the extract, and the tube formation was observed and photographed using an inverted microscope at 4 h and 6 h. ImageJ software was used to analyze the number of tube nodes and the total tube length in each group of images.
[0066] LAPF mesh coating in vitro osteogenic differentiation:
[0067] Alkaline phosphatase (ALP) staining: BMSCs cells were digested and centrifuged, then stained with 2.5 × 10⁻⁶ cells. 4 Seeds were applied to each coating at a density of 1 cell / mL and placed in a cell culture incubator. When the cell density reached 80% confluence, the complete culture medium was removed and osteogenic induction medium was added for continuous culture for 7 days. The medium was partially changed every 2 days. After 7 days, the culture medium was gently removed, and the cells were washed twice with PBS and fixed with 4% paraformaldehyde tissue fixative for 30 min. After removing the fixative, staining was performed according to the Beyotime BCIP / NBT alkaline phosphatase kit instructions for 3-6 h. The color was observed after staining with PBS and the cells were observed and photographed under an inverted microscope.
[0068] Alizarin Red ARS Staining: The culture process was the same as the alkaline phosphatase staining process described above. Cells were cultured in an incubator for 21 days, with a half-medium change every 2 days. The culture medium was removed, and the cells were washed with PBS. The cells were then stained with 4% alizarin red dye for 30 minutes according to the instructions. The staining was then stopped by washing with PBS. The cells were observed and photographed under an inverted microscope. All the experimental results were used to perform quantitative analysis of ALP and ARS calcium nodules by measuring the stained area using ImageJ software.
[0069] In osteogenic mineralization, ALP is one of the earliest markers. Under alkaline conditions, it catalyzes the decomposition of phosphate, producing an insoluble blue-purple precipitate; the deeper the staining, the higher its activity. Figure 7As shown, the control group exhibited a lighter, pale purple staining, indicating that under basal induction conditions, only some BMSCs initiated osteogenic differentiation, and ALP activity was low. The (TA / LAPF)4 coating group stained more deeply than the control group, with a more pronounced color. The (TA / LAPF)8 coating group showed significantly enhanced staining depth, exhibiting a deep blue-purple color, indicating that with increasing TA and LAPF loading in the coating, its effect on promoting osteogenic differentiation was further enhanced. (TA / LAPF)8+Mg 2+ The coating group showed the deepest staining and the most concentrated color, indicating that Mg... 2+ The introduction of [the substance] produced a strong synergistic effect, greatly stimulating the early osteogenic differentiation activity of BMSCs and showing a beneficial effect on early osteogenic mineralization.
[0070] Calcified nodules are calcified matrix formed during osteoblast matrix mineralization and are another cellular characteristic indicator reflecting later osteogenic differentiation capacity. Figure 7 As shown in the alizarin red staining images of the control group, a small number of sparse calcium nodules were observed. The calcium nodule content was slightly increased on the surface of the (TA / LAPF)4 group. Compared to the (TA / LAPF)4 coating, the (TA / LAPF)8 coating showed a large number of dense red calcium nodules, which may be attributed to the increased number of layers. Amyloid proteins can act as templates for biomimetic mineralization, promoting the formation of calcium phosphate, similar to the guiding role of collagen fibers in mineralization. More noteworthy is the presence of Mg-loaded... 2+ The subsequent coating showed a darker color and the largest mineralized area compared to other groups of calcium nodules, demonstrating the best osteogenic mineralization effect. Mg 2+ Bone mineralization can be enhanced through direct or indirect mechanisms, consistent with the aforementioned ALP staining results. Therefore, the introduction of Mg into the TA / LAPF coating... 2+ It not only improved vascularization but also effectively enhanced osteogenic mineralization of BMSCs.
[0071] Example 2
[0072] Weigh 0.05 g of lyophilized LAPF sample, tannic acid (TA), and polyethyleneimine (PEI). The LAPF sample was dissolved in 50 mL of deionized water, while TA and PEI were dissolved in 10 mM NaAc-HAc acetate buffer (pH=6), each at a concentration of 1 mg / mL. First, the titanium scaffold substrate was immersed in the PEI solution for approximately 1 h to form an initial layer. Subsequently, the substrate was alternately immersed in TA solution for 30 min, followed by immersion in LAPF solution for 30 min, labeled as (TA / LAPF). nHere, n represents the number of bilayer cycles. In this embodiment, 4-layer and 8-layer structures (TA / LAPF)4 and (TA / LAPF)8 were used to investigate the effect of the number of layers. Furthermore, between each layer in the layer-by-layer self-assembly process, the sample was washed with 10 mM NaAc-HAc (pH=6) assembly buffer. Finally, the (TA / LAPF)8 coating was immersed in MgCl2 solution (200 mM) for 30 min to incorporate Mg. 2+ And labeled as (TA / LAPF)8+Mg 2+ .
[0073] Scanning electron microscopy (SEM) was performed. The results showed that after surface modification, the titanium scaffold (solid rod, such as...)... Figure 8 Woven netting, such as Figure 9 Micro- and nano-porous structures were formed on the surface of (TA / LAPF). The results indicate that... n +Mg 2+ The coating can be applied to titanium alloy supports of different shapes, demonstrating good substrate versatility.
[0074] Test Example 2
[0075] The specific steps for establishing a rat model of infectious femoral defect with critical skull size are as follows: A titanium rod (2 mm in diameter) was sanded and ultrasonically cleaned for 5 min each in acetone, ethanol, and deionized water, followed by UV irradiation for 15 min. Second-generation Staphylococcus aureus bacterial suspension was diluted with LB liquid medium to a concentration of approximately 1 × 10⁻⁶. 8 CFU / mL and coated titanium rods were co-cultured in a 37 ℃ constant temperature oven for 24 h to form a bacterial biofilm, with the modified coating serving as a control. Rats were anesthetized by intraperitoneal injection of 30 mg / kg anesthetic and underwent surgery on a surgical mat after the rats were in a deep coma. First, the hair on the femur of the rats was shaved and disinfected with povidone-iodine. Then, a longitudinal incision was made along the lateral side of the left femur, and the muscle tissue was bluntly dissected with a scalpel to expose the femoral ankle. At the distal end of the femur, a femoral defect with a diameter of 2.2 mm and a depth of 4 mm was drilled vertically at a low speed, continuously flushed with physiological saline during drilling to remove blood and bone debris. Next, a coated composite titanium rod covered with Staphylococcus aureus was implanted into the bone defect, ensuring complete embedding. The muscle layer and skin tissue were then sutured sequentially. The right femur bone defect was created using the same method, and a blank titanium rod without coating and covered with Staphylococcus aureus was implanted as a control. The surgical area was thoroughly disinfected again with povidone-iodine. Five parallel samples were set up for each experiment. Each rat was injected intramuscularly with 100,000 units of penicillin for three consecutive days post-surgery. Animals were sacrificed one week post-surgery, and samples were collected for subsequent pathological analysis.
[0076] Flat plate coating experiment:
[0077] One week after implantation, rats were euthanized under overdose anesthesia. The femur with the coated titanium implant was removed, and the surrounding tissue was immersed in 7 mL of sterile PBS. Each group was vortexed for 5 min and sonicated for 10 min, and the above steps were repeated twice to ensure that the cells on the tissue and titanium rod were dispersed in the PBS. The PBS was serially diluted, and 100 μL of bacterial culture was taken and evenly spread on LB solid medium. The medium was sealed with film, inverted in a constant temperature oven overnight, and the number of colonies formed was photographed and recorded.
[0078] One week after implantation of coated titanium rods into the femur of rats, bone tissue and titanium implants were removed, and the titanium rod coating and (TA / LAPF)8+Mg were collected, respectively. 2+ Bacteria on the coating surface and surrounding bone tissue were plate-counted. Figure 10 As shown, after 24 hours of cultivation, the number of colonies in the uncoated titanium rod control group was significantly higher than that in the coated group, and quantitative calculations showed that the number of colonies in the control group was approximately five times that of the coated group. This indicates that (TA / LAPF)8+Mg 2+ The coating has a significant inhibitory effect on bacterial infection.
[0079] Osteointegration promotion is a key capability for bone implants to achieve long-term stability. Evaluation was performed 6 weeks after implantation in an infected environment using micro-computed tomography (MCT) and histology. Micro-CT was used to evaluate the control group and (TA / LAPF)8+Mg. 2+ An important means of new bone formation around implants. For example... Figure 11 As shown, it can be clearly observed that (TA / LAPF)8+Mg under infected conditions 2+ The implant was surrounded by almost no gaps and was covered by a large amount of newly formed bone tissue. In contrast, the control group implant was surrounded by only a small amount of newly formed bone tissue.
[0080] like Figure 11 The results showed that (TA / LAPF)8+Mg 2+ The BV / TV value of the group was significantly higher than that of the control group. The results indicate that (TA / LAPF)⁸+Mg 2+ The coating can significantly promote the regeneration and repair of infected bone defects in vivo under bacterial infection conditions.
[0081] Six weeks post-surgery, bone regeneration at the infected bone defect site was further assessed using H&E and Masson staining.
[0082] H&E staining:
[0083] Paraffin sections were dewaxed in xylene for 10 min. The dewaxing process was repeated twice with fresh xylene. Then, a gradient alcohol hydration process was performed, immersing the sections in 75%, 85%, 95% ethanol, and anhydrous ethanol for 5 min each. Hematoxylin staining was then applied to the sections for 8 min, followed by rinsing with deionized water for 1 min. The sections were then immersed in differentiation solution for 10 s, followed by rinsing with deionized water for 1 min. They were then inverted with blue inversion solution for 40 s, followed by rinsing with deionized water for 1 min. Eosin ethanol staining was applied to the sections for 2 min, followed by rinsing with pure water for 1 min to terminate the staining. After dehydration by immersion in anhydrous ethanol, 95% ethanol, and 85% ethanol for 20 s, followed by two cycles of xylene dehydration for 2 min each, the sections were mounted and stored with neutral resin.
[0084] Masson staining:
[0085] Paraffin sections were dewaxed and hydrated using the same method as for H&E staining. After hydration, the sections were stained. First, following the Masson staining kit instructions, A1 and A2 were mixed at a volume ratio of 1:1, then dropped onto the sections for 10 min. The sections were rinsed with running water to remove the stain. Differentiation was performed using acidic differentiation solution for 30 s, followed by rinsing with running water. The sections were then treated with bluing solution for 5 min, and excess stain was removed with a 2-fold diluted weak acid solution. Next, poinsettia solution was added for 10 min, and excess dye was washed away with weak acid. The sections were then treated with phosphomolybdic acid solution for 2 min, washed with weak acid, and finally treated with aniline blue solution for 2 min, washing away excess dye with weak acid to stop the staining process. The sections were then dehydrated by soaking in anhydrous ethanol, 95% ethanol, and 85% ethanol for 20 s, followed by two cycles of xylene for 2 min each time. Finally, the sections were mounted and stored with neutral resin.
[0086] The implanted femur was stained using H&E and Masson staining, such as Figure 12 As shown, under low magnification, the control group and (TA / LAPF)8+Mg 2+ New bone formation was observed at the edges of the bone defects in all coated groups, but its (TA / LAPF)8+Mg 2+ The area and amount of new bone in the coated group were greater than those in the control group. High-magnification magnification of the new bone formation sites revealed (TA / LAPF)8+Mg. 2+ The coated group showed abundant osteoblast formation, with osteoblasts arranged in rows on the new bone formation surface and rich in irregularly woven collagen fibers—all significant markers of new bone formation. In contrast, the control group showed fewer osteoblasts, with almost none observed. Therefore, (TA / LAPF)8+Mg 2+The coating group showed higher osteogenic capacity than the control group. This was because bacterial infection in the control group lacked antibacterial ability, hindering the fusion of the implant with host tissue and severely impacting subsequent bone defect repair and new bone formation. Meanwhile, (TA / LAPF)8+Mg... 2+ Due to the antibacterial properties imparted by the surface coating, the coating group effectively combated in vivo infections and inflammation, resulting in higher levels of tissue repair and new bone formation on the material surface compared to the control group.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A biomimetic mesh nanofiber composite coating, characterized in that: The composite coating is formed by the alternating deposition of positively charged lysozyme amyloid protein fibers and polyphenolic substances on the surface of the implant substrate through layer-by-layer self-assembly, creating a network of nanofibers. The composite coating also includes bioactive metal ions. The composite coating has a micro- and nano-porous hydrophilic surface, with bioactive metal ions loaded and uniformly distributed therein, and coordinated with the polyphenolic hydroxyl groups of the polyphenolic substances. The bioactive metal ions are Mg. 2+ The polyphenolic substance is tannic acid.
2. The composite coating according to claim 1, characterized in that: The composite coating has 4-8 layers.
3. The method for preparing the biomimetic mesh nanofiber composite coating according to claim 1, characterized in that: The preparation steps are as follows: S1: Prepare a 50mM glycine aqueous solution, adjust the pH of the solution to 2, dissolve lysozyme in the glycine solution and mix well. The lysozyme concentration is 10mg / mL. Heat and stir at 65℃ for 0.5-4 h, then transfer to a dialysis bag for dialysis. After freeze-drying, obtain lysozyme amyloid protein fibers. S2: Lysozyme amyloid fibrous material, polyphenolic substances and polyethyleneimine were dissolved in 10 mM acetate buffer NaAc-HAc, respectively. The substrate was immersed in the polyethyleneimine solution for about 1 hour to form an initial layer. Subsequently, the substrate was alternately immersed in the polyphenolic substance solution for 0.5 hours and the lysozyme amyloid fibrous material solution for 0.5 hours to prepare a layered self-assembled network nanofiber structure coating. S3: Immerse the mesh nanofiber structure coating prepared in step S2 in a bioactive metal ion solution for 0.5 h to form the mesh nanofiber composite coating.
4. The preparation method according to claim 3, characterized in that: The concentrations of the lysozyme, amyloid cellulose, polyphenols, and polyethyleneimine are 1-10 mg / mL.
5. The preparation method according to claim 3, characterized in that: The substrate is any one of stainless steel, magnesium alloy, or titanium alloy support.
6. The application of the biomimetic mesh nanofiber composite coating according to any one of claims 1-2 in the preparation of medical materials or drugs.
7. The application of the biomimetic mesh nanofiber composite coating according to any one of claims 1-2 in the preparation of medical materials for infectious bone defects.
Citation Information
Patent Citations
Induction method of lysozyme amyloid fiber model
CN110904080A
Intravascular stent coating based on phase transition lysozyme membrane loaded copper ions and heparin and preparation method of intravascular stent coating
CN116764002A